Renegade Lawyer: The Life of J.l. Cohen - MacDowell, Laurel Sefton (Published for the Osgoode Society for Canadian Legal History by University of Toronto Press, 2001)
J.L. Cohen, one of the first specialists in labour law and an architect of the Canadian industrial relations system, was a formidable advocate in the 1930s and 1940s on behalf of working people. A 'radical lawyer' in the tradition of the great American counsel Clarence Darrow or contemporary advocate Thomas Berger who represent the less powerful and seek to reform society and to protect civil liberties, Cohen was also a 'labour intellectual' in Canada, similar to those supporting Roosevelt's New Deal in the United States. He wrote Collective Bargaining in Canada, served on the National War Labour Board, and advised the Ontario government about policy issues such as mothers' allowances, unemployment insurance legislation, and labour law..